Banking Competition, Financial Liberalization and Economic Growth: Evidence from Turkish Economy during the 1990-2014 Period - Çelik, Tuncay; Citak, Levent (International Journal of Economics and Financial Issues, 2016)
After 1950s, economics literature embraced a gradually increasing pattern of studies on economic growth. Empirical studies on the relations among competition in the banking sector, which provides financing to real investments, financial liberalization and economic growth have been increasing since late 1980s. These studies, which have their roots in McKinnon and Shaw approach, investigate whether financial liberalization leads to efficiency rise in the financial sector resulting in economic growth through low cost loans. The objective of this study is to test the relationship among competition in the Turkish Banking Sector, financial liberalization and economic growth over 1990-2014 period using annual time-series data. The findings suggest that over the study period, competition is positively and liberalization is negatively related to economic growth in Turkey. Keywords: Banking competition, H statistics, liberalization, economic growth, Turkish economy JEL Classifications: G21, L11, O11